Methionine-ethylenediaminetetraacetic acid-chitosan magnetic nanocomposite: A multifunctional organocatalyst for green heteroannulation of imidazoles - Mohammad G. Dekamin; Mohammad Dohendou; Danial Namaki; Zahra Dehnamaki; Suranjana V. Mayani (Carbohydrate Polymer Technologies and Applications)
Straightforward procedure for the preparation of a novel magnetic decorated DL-methionine amino acid grafted onto the chitosan backbone using EDTA linker (CS−EDTA−MET@Fe3O4) is described. The supramolecular CS−EDTA−MET@Fe3O4 nanocomposite was properly characterized using FTIR, EDX, XRD, FESEM, TGA, DTA and VSM methods. The obtained CS−EDTA−MET@Fe3O4 nanomaterial was then investigated, as a multifunctional heterogeneous organocatalyst, to promote the heteroannulation of a wide range of imidazoles through multicomponent reactions strategy. The three- and four-substituted imidazole derivatives, as an important pharmaceutical scaffold, were smoothly synthesized from benzoin or benzil, different aldehyde derivatives, and NH4OAc as well as aromatic or aliphatic amine derivatives in EtOH. The CS−EDTA−MET@Fe3O4 nanocatalyst exhibited high catalytic activity, selectivity, and stability to promote the multi-component condensations. The key advantages of the present protocol are high to excellent yields, the use of a low loading renewable, bio-based and biodegradable chitosan- as well as amino acid-based nanomaterial, and simple procedure for the preparation of CS−EDTA−MET@Fe3O4 nanomaterial. In addition, the catalyst's properties including its magnetic properties and appropriate surface area characteristics contribute to its excellent catalytic performance. Furthermore, the CS−EDTA−MET@Fe3O4 nanocatalyst can be used for up to six cycles in the synthesis of imidazole derivatives with only a slight decrease in its catalytic activity.